2020
DOI: 10.1093/jpids/piaa086
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome Associated With Severe Acute Respiratory Syndrome Coronavirus 2 Detection and Coronavirus Disease 2019 in a Child

Abstract: Abstract Coronavirus disease (COVID-19) is caused by SARS-CoV-2. Physicians in China reported what is believed to be the first adult case of a SARS-CoV-2 infection associated with acute Guillain-Barré syndrome (GBS), followed by five adult Italian patients and another case in the United States of America. In the current report we present one of the first descriptions of an association of GBS and SARS-CoV-2 infection within a child. In our facility, and eleven ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
1
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 7 publications
(7 reference statements)
0
88
1
9
Order By: Relevance
“…In the present study, mean age at onset in patients with GBS largely overlapped that of classic COVID-19 subjects [70,71]. However, pediatric cases with GBS have been increasingly reported in the literature [21,27,35,41], suggesting that, with the spreading of the pandemic, a broader age range might be affected. Moreover, we found a higher prevalence of GBS in males compared to females, as previously reported for Zika virus-GBS [72].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In the present study, mean age at onset in patients with GBS largely overlapped that of classic COVID-19 subjects [70,71]. However, pediatric cases with GBS have been increasingly reported in the literature [21,27,35,41], suggesting that, with the spreading of the pandemic, a broader age range might be affected. Moreover, we found a higher prevalence of GBS in males compared to females, as previously reported for Zika virus-GBS [72].…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, brainstem leptomeningeal enhancement was described in two cases with AIDP, both with clinical cranial nerve involvement [18,46]. On the other hand, spinal nerve roots and leptomeningeal enhancement were reported in eight [9,27,31,36,37,42,52] and two cases [17,46], respectively ( Table 1).…”
Section: Results Of Electrophysiological Csf Biochemical and Neuromentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, lower limb weakness and paresthesia that may lead to generalized tetraparesis or tetraplegia evolving over a period of several days have been repeatedly observed [ 92 ]. Typically, MRI performed with the administration of gadolinium reveals enhancement of the cauda equina nerve roots on postcontrast findings and asymmetrical thickening and hyperintensity of postganglionic roots of the brachial and lumbar plexuses [ 93 , 94 ]. Moreover, cytoalbuminologic dissociation of the CSF is a characteristic finding in GBS, pointing to nerve root involvement.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Demirci Otluoglu et al noted CSF protein was 0.4 mg/L (0.04 mg/dL) and Dharsandiya et al indicated the CSF protein was 39 g/dL (3,900 mg/dL), but both authors described the protein as normal, and Matos et al reported a CSF protein of 0.78 mg/dL, but noted it was mildly elevated; we presumed these were meant to be 0.4g/L (40 mg/dL), 39 mg/dL, and 78 mg/dL, respectively [ 150 , 151 , 200 ]. There were 27/397 (7%) patients who had CSF protein >200 mg/dL (19/27 (70%) with symptoms that localized to the CNS and 8/27 (30%) with symptoms that localized to the PNS) [ 16 , 21 , 31 , 32 , 34 , 44 , 53 , 58 , 78 , 81 , 89 , 104 , 113 , 127 , 128 , 160 , 170 , 173 , 176 , 184 , 199 , [220] , [221] , [222] , 245 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%